2021
DOI: 10.3390/plants10112347
|View full text |Cite
|
Sign up to set email alerts
|

Cornus mas and Cornus officinalis—A Comparison of Antioxidant and Immunomodulatory Activities of Standardized Fruit Extracts in Human Neutrophils and Caco-2 Models

Abstract: Fruits of Cornus mas and Cornus officinalis are representative plant materials traditionally used in Europe and Asia, respectively, in the treatment of diabetes and diabetes-related complications, which are often mediated by pathogenic inflammatory agents. Additionally, due to the fact of mutual infiltration of Asian and European medicines, the differentiation as well as standardization of traditional prescriptions seem to be crucial for ensuring the quality of traditional products. The objective of this study… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 72 publications
0
11
0
Order By: Relevance
“…The other constituent components, iridoids and their glycosides, show a wide range of t actions such as cardiovascular, hypoglycemic, hypolipidemic, antioxidant, anti-inflammatory, immunomodulatory action, etc. [ 8 , 31 , 32 ]. Rational use of plant extracts in treatment will be possible if we understand the mechanism of their action on biological systems at the molecular and cellular levels.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The other constituent components, iridoids and their glycosides, show a wide range of t actions such as cardiovascular, hypoglycemic, hypolipidemic, antioxidant, anti-inflammatory, immunomodulatory action, etc. [ 8 , 31 , 32 ]. Rational use of plant extracts in treatment will be possible if we understand the mechanism of their action on biological systems at the molecular and cellular levels.…”
Section: Resultsmentioning
confidence: 99%
“…However, the latter includes more iridoids and phenolic acids [ 7 ]. The constituent components of extracts from Cornus mas L. exhibit a variety of biological activities, making the extract a promising compound in the treatment of various diseases, especially gastrointestinal and metabolic disorders, diabetes and diabetes-related complications, stomach ulcers, diarrhea, fever, sore throats, urinary tract infections and liver and kidney diseases [ 8 , 9 ]. Moreover, little is known about the biological effects of extract of yellow fruits of Cornus mas L., in comparison with extract of red fruits of Cornus mas L.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Caco-2 cells were cultured in DMEM supplemented with 20% FBS (v/v), L-alanyl-L-glutamine (2 mM), penicillin (100 IU/ ml), streptomycin (100 μg/ml), and amphotericin B (2.5 ng/ml). The details of cell culturing were previously described (Czerwińska et al, 2021). Passages between 20 and 45 were used in all in vitro experiments.…”
Section: Caco-2 Cell Culturementioning
confidence: 99%
“…Both cornuside and loganic acid have also been proven to suppress those cytokines’ activity [ 16 , 17 ]. In our previous study, it was shown that in human neutrophils ex vivo and colon adenocarcinoma cell line in vitro cornelian cherry significantly reduced the level of IL-8 [ 18 ], which is a chemoattractant involved in the development of inflammatory process [ 19 ]. Furthermore, according to clinical data, the consumption of C. mas extract resulted in a decrease of highly sensitive C-reactive protein (hsCRP) in postmenopausal women [ 20 ].…”
Section: Introductionmentioning
confidence: 99%